(untitled) - Kramer, Bill (Lawrence, 2002)
Customize AutoCAD to include productivity enhancements such as new commands, combinations of existing commands, or list processing scripts for the storage and manipulation of data. This tutorial offers a complement of AutoLISP programming skills - from the basic concepts to advanced programming techniques - that you can use to enhance your AutoCAD 2000, 2000i, and 2002 environments.
Keywords: Computer graphics,Visual LISP (Computer program language),Đồ họa máy tính,LISP